A novel highly specific colorimetric fluorescent probe for the detection of nitrite in aqueous solution. (3rd March 2022) - Xu, Jing; Shi, Yanfeng; Xu, Gongwei; Zhao, Qinrui; Hui, Li; Zhang, Shuo; Zhu, Baocun; Xu, Zhenghe; Bian, Zhen
Abstract: Developing an effective method for the detection of nitrite (NO2 − ) ions in the natural environment especially in environmental waters and soils is very necessary, since they will cause serious damage to human health once excess NO2 − ions enters the human body. Therefore, a new colorimetric fluorescent probe NB‐NO2 − for determining NO2 − ions was designed, which possesses good water‐solubility and satisfactory selectivity over other common ions for NO2 − ions. The addition of NO2 − ions changed the color of solution from blue to colorless seen by the naked‐eye. Furthermore, through test and calculation, the detection limit of the probe NB‐NO2 − is 129 nM. Based on the earlier excellent characteristics, the probe NB‐NO2 − was successfully used for monitoring NO2 − ions in environmental waters and soils. Abstract : A novel colorimetric fluorescent probe was developed to monitor nitrite (NO2 − ) ions in environmental waters and soils which possessed many excellent characteristics, including naked‐eye detection, high selectivity, good water‐solubility, near‐infrared emission ( λ em = 672 nm) and excellent application in the practical environment.